PEMANFAATAN PENGERING EFEK RUMAH KACA DALAM MENINGKATKAN KUALITAS KERUPUK KASUBI LONUO BUKIT ARANG - Fuad Pontoiyo; Burhan Liputo; Yunita Djamalu (Program Vokasi Universitas Negeri Gorontalo, 2024)
Lonuo Village is located in Tilongkabila District, Bone Bolango Regency, Gorontalo. Kasubi crackers are a typical snack produced by one of the Lonuo Bukit Arang Kasubi Crackers UKMs. Kasubi crackers are made from cassava, tapioca flour, baking soda, and brown sugar, while other production requirements are cooking oil, LPG gas, gasoline, firewood, raffia rope, and plastic packaging. Meanwhile, other supporting tools in the kasubi cracker production process are plastic plates, steamer frames, steaming pans, molding tanks, sweet potato grinding machines, and para-paras as attachments for manual drying. The manual drying place used by IKM consists of 3 bamboo-based lamps measuring 7 x 13 meters for the entire cracker drying place. The drying process using bamboo sheets has many disadvantages, including drying time which takes 4 to 5 drying hours in sunny weather, unpredictable weather, less hygienic, and tends to be contaminated with bacteria because the location of the IKM is opposite the location of the Final Processing Site (TPA) for waste disposal. Bone Bolango Regency. The Kasubi Lonuo Bukit Arang cracker IKM was established in 2000 and has been continued by Santian Pillow since 2020. This IKM has more than 6 (six) permanent and non-permanent employees with daily raw material production of 1 () sack of cassava Working time from grating the coconut to drying takes 8 to 9 hours, namely from 08.00 to 15.00 WITA with the resulting cracker output being 2448 crackers per day and packaged in one hanging containing 10 crackers and priced at IDR. 11,000 per hanging. The method used in this activity is the preparation stage, implementation of activities, and program sustainability plans. The alternative drying tool that will be socialized in this activity is a greenhouse drying tool in the form of a rectangular prism with the help of energy from sunlight. While serving this community group, the service team packages activities from lecture presentations on introducing tools, questions, and answers, how to make tools, how to use tools, and how to maintain tools. From the results of this activity, it was agreed that the next activity would focus more on making cracker products using biomass stoves or stoves fueled by used oil and greenhouse effect dryers.